2001
DOI: 10.1001/jama.285.13.1736
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cancer With AIDS-Related Immunosuppression in Adults

Abstract: Although occurring in overall excess, most non-AIDS-defining cancers do not appear to be influenced by the advancing immunosuppression associated with HIV disease progression. Some cancers that met our criteria for potential association with immunosuppression may have occurred in excess in persons with HIV/AIDS because of heavy smoking (lung cancer), frequent exposure to human papillomavirus (penile cancer), or inaccurately recorded cases of Kaposi sarcoma (soft tissue malignancies) in these persons. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
486
3
17

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 744 publications
(526 citation statements)
references
References 40 publications
20
486
3
17
Order By: Relevance
“…Whereas MCCHL and LDCHL were strongly associated with HIV infection, all NSCHL, the most commonly diagnosed HL type in Rwanda, were HIV negative. This is consistent with studies in high‐income settings,21, 22, 23 but is the first formal report from sub‐Saharan Africa.…”
Section: Discussionsupporting
confidence: 91%
“…Whereas MCCHL and LDCHL were strongly associated with HIV infection, all NSCHL, the most commonly diagnosed HL type in Rwanda, were HIV negative. This is consistent with studies in high‐income settings,21, 22, 23 but is the first formal report from sub‐Saharan Africa.…”
Section: Discussionsupporting
confidence: 91%
“…15 In addition, studies have found that vulva, vagina, penile, oral cavity, and pharynx cancers are caused by HPV, with limited association with cancer of the larynx. 11,21,25,35 Interestingly, previous studies have found a link between virus-related cancers such as HL, 27 HCC, 28 and anal cancer 26 with immunodeficiency determined by time to AIDS diagnosis 26,27 or CD4 count within 1 year of diagnosis. 28 The most common non-virus-related epithelial cancers (eg, lung and prostate) remain difficult to treat, and the majority remain incurable, with very little improvement in survival over the past decade 36 ; in addition, based on oncoepidemiologic studies, risk of epithelial cancers starts to increase at about the age of 30 years and increases progressively by age.…”
Section: Discussionmentioning
confidence: 99%
“…23 A similar linkage-based population study examining more than 300 000 people throughout the United States aged 15-69 years demonstrated a lower than expected incidence of PCa both in the overall (RR 0.7; 95% CI 0.6-0.9) and post-AIDS onset period (RR 0.5; 95% CI 0.4-0.7). 24 Based on these and several other large retrospective population-based studies, it is difficult to determine if there is an increased or decreased incidence of HIV in an age-matched general population. 25,26 These observationbased, epidemiologic studies simply look at incidence of PCa in an HIV-positive cohort which is dependent on detection and, thus, PSA and DRE screening.…”
Section: Prostate Cancermentioning
confidence: 99%
“…42 HAART may prove to be protective against the development of PCa and this may in part explain the reduced incidence of PCa seen in several of the large epidemiological studies outlined earlier. [23][24][25] It is interesting to note that several of the recently published studies of HIV-positive men with PCa did occur while these patients were receiving HAART. Pantanowitz et al noted that 82% of the men with HIV and PCa were receiving HAART, and Ng et al noted that 79% were receiving HAART.…”
Section: Highly Active Antiretroviral Therapymentioning
confidence: 99%